Biodiversity of Fishes in Musi Estuary, South Sumatra, Indonesia - Fitri Agustriani; Anna Ida Sunaryo Purwiyanto; Wike Ayu Eka Putri; Fauziyah Fauziyah (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2020)
Agustriani F, Purwiyanto AIS, Putri WAE, Fauziyah F. 2020. Biodiversity of fishes in musi estuary, South Sumatra, Indonesia.Â  Jurnal Lahan Suboptimal : Journal of Suboptimal Lands 9(2): 192-198.The high activity in the Musi estuary will have an impact on fishes diversity. This research aimed to analyse the biodiversity of fishes in the Musi estuary in South Sumatra. An experimental fishing method was used for data collection by fishing ground following the local fishermen habit using gillnet millennium. The abundance of fish species found were 21 species and 16 families. The main catch was Hemibagrus nemurus with a high relative abundance (RA) of 35.4% but the high availability frequency of 100% is Eleutheronema tetradactylum. The average value of the moderate diversity index (H'= 1.47), the moderate evenness index (J'= 0.48) and the low dominance index (D= 0.32). This condition shows that the community structure of the species captured by the gill net is in a fairly stable condition with the number of species that are spread fairly evenly and no species dominate each other.